Factors Influencing Public Higher Education Institutions’ Performance Reporting in the Romanian Context - Adriana Tiron-Tudor; Cristina Silvia Nistor; Szilveszter Fekete; Andreea Alexandru (Administrative Sciences, 2022)
Our study aims to facilitate a deeper understanding of the factors influencing performance reporting in the specific context of the hybrid higher education system in Romania, a former communist country in Eastern Europe with little experience in managing the notion of public sector performance. Performance reporting impacts higher education institutions’ development. The study’s approach offers opportunities to understand the main factors that influence and are influenced by mandatory elements stipulated in the specific norms in the public-university domain. Institutional and operant theories explain and sustain multilevel (institutional, organizational, and individual) performance-reporting analysis. In terms of research design, the theoretical exploration led us to formulate hypotheses while empirical data were collected from 23 Romanian public universities, ensuring the results’ reliability. The results indicate that the performance-reporting concept and practical demand in public universities depend on both exogenous causes (isomorphic pressures) and endogenous factors (different behaviors of organizations and individual performers). The performance reporting of Romanian public higher education institutions enriches the scientific literature and the practical sphere by offering comprehension of a European country’s evolution with roots in a communist system, having a lot of specific approaches, as a base for comparison with similar Eastern European entities or experienced countries.